Optimized virtual fields with noise minimization - Syed Muhammad, Kashif (International Islamic University Malaysia Press, 2011)
This chapter discusses numerical issues in noise minimization and a representative cost function to be minimized. Such a minimization helps in finding a unique and optimized set of unknown bending rigidity that is least sensitive to noise. This chapter presents an optimized identification procedure with minimum noise sensitivity and its adaption for simultaneous identification of the unknown bending rigidities of a thin anisotropic plate.